PENGARUH LOYALITAS DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. BANK BENGKULU CABANGREJANG LEBONG - Jaya, Aldi Putra; Indriani, Reni (UM. Bengkulu, 2025)
This study entitled The Effect of Loyalty and Competence on Employee Performance at PT. Bank Bengkulu Chapter Rejang Lebong. The purpose of this study was to dtermine whether thres is an effect of Loyalty and Competence on Employee Performance at PT. Bank Bengkulu Chapter Rejang Lebong. This study uses quantitative methods and data collection by means of observation, interviews and questionnaires. The population in this study were all employees of PT. Bank Bengkulu Chapter Rejang Lebong collected as many as 35 peopel and sampling using the total sampling method. Based on the results of multiple linear regression, the regression equation form Y = 1.010 + 0.179 (X1) + 0.580 (X2). This equation can be explained by the positif influencer of each independent variabel, namely Loyalty (X1) and Competence (X2) on Employee Performance (Y) and the coefficient of determination R2 = 0.992 or (99.2 %) through testing hypotheses together (Simultaneously) and individually (partial) in this study using the f test and t test, namely Loyalty (X1) and Competence (X2) = 0,000, meaning that fsig value < 0,05 indicates significantly together and have a significant effect. Keyword : Loyalty, Competence, Employee Performance